2015
DOI: 10.7554/elife.10766
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella adenylate cyclase toxin is a unique ligand of the integrin complement receptor 3

Abstract: Integrins are heterodimeric cell surface adhesion and signaling receptors that are essential for metazoan existence. Some integrins contain an I-domain that is a major ligand binding site. The ligands preferentially engage the active forms of the integrins and trigger signaling cascades that alter numerous cell functions. Here we found that the adenylate cyclase toxin (CyaA), a key virulence factor of the whooping cough agent Bordetella pertussis, preferentially binds an inactive form of the integrin complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(129 citation statements)
references
References 84 publications
5
123
0
Order By: Relevance
“…The ACT species selectivity and truncation data suggested a role for RTX blocks II–III, while earlier work suggested that the receptor-binding region lies between RTX residues 1166–1287 that span blocks II–III. 15, 30 We amplified codons 751–1358 (about two-thirds of RTX 751 ) under error-prone conditions. A library with 2.1 × 10 7 clones was constructed using homologous recombination of Nhe I/ Sph I linearized vector backbone and error prone PCR product with overhangs on both ends.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACT species selectivity and truncation data suggested a role for RTX blocks II–III, while earlier work suggested that the receptor-binding region lies between RTX residues 1166–1287 that span blocks II–III. 15, 30 We amplified codons 751–1358 (about two-thirds of RTX 751 ) under error-prone conditions. A library with 2.1 × 10 7 clones was constructed using homologous recombination of Nhe I/ Sph I linearized vector backbone and error prone PCR product with overhangs on both ends.…”
Section: Resultsmentioning
confidence: 99%
“…The sole shared residue is indicated by bold and purple. Bold, underlined and italized residues indicate those implicated in receptor binding 30 . The boxes indicate the first three Gly-Asp rich repeat blocks.…”
Section: Figurementioning
confidence: 99%
“…It is worth noting that, besides interfering with the bottleneck step at the level of PLC activation, the CyaA-generated cAMP signaling can provoke inhibition of the ROS-inducing pathways also upstream of PLC, at the level of signaling of opsonin receptors. Indeed, we have recently found that CyaA-generated cAMP signaling provokes inactivation of Syk in human monocytes, thereby interfering with the iC3b-activated prophagocytic and ROS-inducing signaling of CR3 through Syk (10).…”
Section: Discussionmentioning
confidence: 99%
“…Upon initial interaction with N-linked oligosaccharides (31,32), CyaA specifically binds a loop outside the I domain of the CD11b subunit of the ␣ M ␤ 2 integrin (CR3) (5), and the toxin delivers the AC enzyme into phagocyte cytosol in two steps (33). Compelling indirect evidence suggests that the AC-translocating and pore-forming activities of CyaA are mutually independent and are accomplished by two distinct subpopulations of CyaA conformers that employ the same transmembrane CyaA segments in an alternative manner (34).…”
mentioning
confidence: 99%